Introduction to the Special Session: Design and Research for Advanced Human Augmentation - Kymalainen, Tiina (Proceedings (International Conference on Intelligent Environments), 2016)
This special session has called for contributions that demonstrate research in advanced human augmentation. The introduction briefly describes how the concept is currently understood, and, in the creative science spirit, depicts how it may be understood in the more distant future. To explain this, the introduction presents a short science fiction prototype that illustrates how future co-creative intelligence will combine human technology with human intelligence by emphasizing the role of human centricity in the advanced human augmentation vision. To achieve an overview of how the vision is currently being pursued, this special session demonstrates contemporary research that advances the ideas. In the session the nominated contribution is limited to the industrial work context, training and mentoring, and assistive augmentation for the elderly and visually impaired. The technological focus is mainly on virtual/mixed/augmented realities, eye-tracking systems and head-mounted displays.